Lives Behind the Faces: Perceived Influence of Families on Female Adult Learners - Paula Plageman (Adult Education Research Conference, 2014)
This qualitative study explored how the perceived influence of members of both the family of origin and current family impacted adult female’s educational experiences. Findings suggest that family of origin significantly impacted attendance as traditionally aged students while supportive current family members enhanced persistence.